Lichens from the Maslak Campus of Istanbul technical university - (:unkn) unknown (My University, 2007)
The lichen diversity of the Masiak Campus of Istanbul Technical University is presented in this study. In total, 23 lichen species belonging to 14 genera were recorded. Strangospora pinicola (A.Massal.) Körb. is a new record for the Turkish lichen flora and 5 species are new records for Istanbul province. © TÜBİTAK.
Keywords: Biodiversity; Istanbul; Lichenised fungi; Turkey